Insecurity Cameras: Cinematic Elevators, Infidelity and the Crime of Time - Thain, Alanna (Intermédialités / Intermediality)

(untitled) (Revue Intermédialités (Presses de l’Université de Montréal), 2009)
The elevator, like the train and other icons of automated movement, would seem to hold a natural affinity with cinema, a kind of machine for making non-habitual space and time. Elevators displace human activity and effort, opening up instead a range of other types of encounters and types of mobility. As time-based mediums, elevators are zones of duration where the potential for change is made manifest. Unlike trains, however, elevators have not received or drawn critical interest on the part of cinema studies. This paper looks at the enduring verticality of cinematic elevators through a Bergsonian sense of duration as “infidelity to the self”, presenting a close reading of the elevator murder in Brian DePalma’s Dressed to Kill (1980) and a broader consideration of the elevator in cinema and urban culture.